2022
DOI: 10.1017/s0022149x22000062
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dirofilaria repens in dogs living in deltaic coastal plain of the Volturno River (Italy): a geographical risk model of infection

Abstract: The prevalence of vector-associated parasitic infections is high in central-southern Italy. The deltaic coastal plain of the Volturno River has been suspected, by veterinary practitioners, to have a high accidental incidence of Dirofilaria repens. Thus, the goal of this study was to evaluate the prevalence of dirofilariasis and other coinfections frequently described in dogs living in the Volturno area. Blood samples of 100 clinical asymptomatic dogs were examined using a Knott's technique and polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The study was conducted in a dog shelter located in Castel Volturno ( Figure 1 ), a deltaic coastal plain of the Volturno River, an area where veterinary practitioners have reported a high incidence of D. repens infection ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study was conducted in a dog shelter located in Castel Volturno ( Figure 1 ), a deltaic coastal plain of the Volturno River, an area where veterinary practitioners have reported a high incidence of D. repens infection ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…The results of the questionnaire survey on heartworm and subcutaneous dirofilariosis addressed to veterinary practitioners throughout Italy ( 7 ) showed that at least one clinical case per year of cardiopulmonary dirofilariosis was diagnosed in dogs with frequent co-infestation by D. immitis and D. repens in Campania. Recent studies confirm the presence of autochthonous cases of D. immitis with a prevalence of approximately 0.1% ( 13 , 17 ). Based on the last two reports of two cases of heartworm disease (HW) detected during post-mortem examination of two roaming dogs ( 17 ) and a screening study in which 10% of dogs tested positive for D. repens ( 13 ), both studies from the urban area of Castel Volturno in the Campania region of southern Italy, the aim of the present study was to describe an outbreak of infection in a dog shelter from the same area.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Dirofilaria repens is the primary species causing canine subcutaneous dirofilariosis, which is endemic in Europe, southeast Asia, and Africa (176,177). It is primarily of zoonotic importance but can be highly prevalent in dogs (178). Similar to other representatives of Dirofilaria, it can be transmitted by numerous mosquito species and may establish in the same areas suitable for D. immitis due to the possibility of competent vector sharing (173).…”
Section: Pathogenicity Clinical Signs and Diagnosismentioning
confidence: 99%